2016
DOI: 10.1002/jmri.25238
|View full text |Cite
|
Sign up to set email alerts
|

Value of severe liver iron overload for assessing heart iron levels in thalassemia major patients

Abstract: Our preliminary data suggest the existence of a close relationship between severe LIO and HIO. High liver iron levels appear to increase the risk of heart iron deposition. This further supports the concept of critical liver iron concentration, above which elevated heart iron is present. J. MAGN. RESON. IMAGING 2016;44:880-889.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…There is a lag in the loading and unloading of heart iron with respect to liver iron in this case, which has been observed by Noetzli et al [31] and Chen et al [32] Jensen et al [33] also points that liver iron concentration threshold (approximately 350 μmol/g) exists, after which chelatable iron pool is allowed to expand to this critical size and iron begins to be deposited in the heart. Noetzli et al [31] explained that elevated liver iron may damage the liver, inhibiting liver non-transferrin bound iron (NTBI) uptake and increasing heart NTBI exposure.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…There is a lag in the loading and unloading of heart iron with respect to liver iron in this case, which has been observed by Noetzli et al [31] and Chen et al [32] Jensen et al [33] also points that liver iron concentration threshold (approximately 350 μmol/g) exists, after which chelatable iron pool is allowed to expand to this critical size and iron begins to be deposited in the heart. Noetzli et al [31] explained that elevated liver iron may damage the liver, inhibiting liver non-transferrin bound iron (NTBI) uptake and increasing heart NTBI exposure.…”
Section: Discussionsupporting
confidence: 61%
“…High liver iron levels seem to increase the risk of heart iron deposition. [32] Furthermore, it is slower and more difficult to remove myocardial iron than hepatic iron, [31] which is obvious for this patient, whose heart iron concentration was only reduced by 0.02 mg/g after bloodletting 1500 mL, whereas liver iron concentration was reduced by 1.03 mg/g.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 17 ] In contrast, several recent studies have demonstrated a less obvious correlation between liver iron concentration and heart iron. [ 15 , 18 ] One possible reason for this disconnection may be an organ-specific mechanism of iron uptake and release. The liver is the natural storage organ for iron and is the most commonly involved organ in patients with iron overload, whereas cardiac involvement is relatively late.…”
Section: Discussionmentioning
confidence: 99%